(untitled) (Global Journal of Human-Social Science, 2013)
This study was designed to investigate Internet usage using factor analytic approach with principal factoring method The principal objective of the study was to determine and identify how many latent constructs actually influence the internet usage the underlying relationship between them Data were collected from 220 Lecturers of higher institutions in Ondo State Nigeria A 30- item questionnaire was designed based on different purposes of internet usage The questionnaire used Likert scale structured questions on internet usage the questionnaire was validated and also confirmed reliable Croubach Alpha 0 67 The findings of the study revealed that 7 factors constitute the dominant influence internal attributes on internet usage Based on the findings it was recommended that Lecturers in Nigerian tertiary institutions should undertake mandatory training and retraining on ICT programmes to provide them with practical and functional knowledge of computer internet and associated area of ICT with the hope of integrating it with the curriculum and instructional methods strategies in teachinglearning process